Shaping the future: science and technology foresight activities in Japan, with special consideration of the 10th foresight - Cuhls, Kerstin (Asien, 2016)
Japan has to date 50 years of experience of national Foresight activities, being performed for science, technology, and for innovation policy formulation purposes. Will Foresight in Japan, as a way of pursuing activity-oriented science and technology (S&T) studies and of contributing to policymaking, be continued? Is it even worth the huge effort? Is it really oriented toward societal issues? Combining the classic approaches and databases that exist, the Foresight procedure can be said to be unique in the world and to have the chance to indeed give answers also to societal questions - and further more to link these answers to the policy system. Whereas the first Forecast/Foresight studies were Delphi surveys only, the methodology has broadened from the 7th Foresight program onward. The year 2001 marked a strong reorganization in the S&T policy landscape, which made a stronger link to the policymaking of the Council of Science and Technology Policy (CSTP, later Council of Science, Technology Policy and Innovation, CSTI) possible. The Japanese strategy "Innovation 25" was also underscored with Foresight results, and the scenarios that had been formulated during the program. Foresight is thus more than prediction; it is rather about shaping the future. This links it directly to S&T studies and gives them a futures drive - instead of only analyzing past experiences. In 2015 the 10th Japanese Foresight was published. The paper describes this new Foresight in brief, and links it to S&T studies broadly - with another connection also made to Japanology, as the backbone of being able to analyze the original sources and to understand the wider Japanese background. Some of the Foresight results are also summarized, and an overview of previous activities in Japan given. Whereas in different countries all over the world Foresight and Horizon Scanning activities are flourishing at present, the Japanese national activities are currently at a crossroads - as policymakers there are not convinced anymore that their model of performance is still necessary in times of the internet and of an information overflow. Therefore, this contribution goes back and forth in time and ends with a brief outlook for Foresight and its actors in Japan.
Keywords: Japan